Multi-port DC circuit breaker based on dual capacitor current limiting and energy sink - Gu, Wei; Lou, Xiansi; Yin, Wenzhe; Huang, Qihang; Li, Shiqiang; Bian, Jing (Frontiers in Energy Research, 2023)
The coupling relationship between the removal of the fault current and the dissipation of the residual energy of the fault line during the fault isolation process of the multi-port capacitive current-limiting DC circuit breaker prolongs the breaking time of the fault to a certain extent. In order to solve the above problems, this paper proposes a multi-port DC circuit breaker based on dual-capacitor current limiting and energy sinking on the premise of decoupling the fault current attenuation and removal process and the fault line residual energy discharge process. Further reduce the fault breaking time and equipment withstand voltage requirements of the DC circuit breaker. Firstly, the topology and working principle of the proposed circuit breaker are analyzed, and then the parameters in the topology are designed. Then a simulation model is built in the PSCAD/EMTDC simulation platform to verify the fault breaking performance and breaking time. The effect of decoupling the fault current clearing process and the fault line residual energy discharge process on the effectiveness of shortening the fault breaking time is verified.